One-step synthesis and electrochemical performance of a PbMoO4/CdMoO4 composite as an electrode material for high-performance supercapacitor applications. Issue 28 (24th June 2019) - Anitha, Tarugu; Reddy, Araveeti Eswar; Anil Kumar, Yedluri; Cho, Young-Rae; Kim, Hee-Je
Abstract : A bunch of PbMoO4 /CdMoO4 nanocube-like structures exhibit superior specific capacitance and cycling stability to PbMoO4 and CdMoO4 electrodes. Abstract : Homogeneously ultrathin nanocubes of PbMoO4 /CdMoO4 nanocomposites, which are useful for energy storage applications, were prepared on nickel foam using a one-step chemical bath deposition method. The capacitive performance of the synthesized PbMoO4 /CdMoO4 electrode material was examined by cyclic voltammetry, galvanostatic charge/discharge, and electrochemical impedance spectroscopy in a three-electrode configuration. This unique structure can provide more electroactive sites and a larger surface area, which can enhance the electrochemical performance. The PbMoO4 /CdMoO4 redox-active material achieved a high specific capacitance of 1840.32 F g −1 at a current density of 1 A g −1 in a 3 M KOH solution. This electrode exhibited excellent long cycle life stability with ∼81.4% specific capacitance retention after 5000 cycles at a current density of 4 A g −1, which is superior to that of individual PbMoO4 and CdMoO4 nanosheets. The prepared PbMoO4 /CdMoO4 composite electrode displayed excellent electrocapacitive properties, which can be attributed to the synergetic effects of PbMoO4 and CdMoO4 . These results suggest that the PbMoO4 /CdMoO4 nanocube arrays have the potential to meet the requirements of practical electrochemical energy storage applications.